Analisis Perhitingan Kapasitas Pompa Sentrifugal Di Pdam Tirta Tarum Karawang - Ali, Nur; Gusniar, Iwan Nugraha (Jurnal Mesin Nusantara, 2023)
Water is a basic need for every living creature, especially society in general. The need for clean water is very important for daily needs. PDAM is a supplier of drinking water as a company that is vital enough to support people's lives. To distribute water from its source to reach the community, a pump is needed as a vital tool to supply this water. With the rapid increase in population, the need for clean water also increases. To find out the water needs, a calculation analysis was carried out to find out the water needs and pump capacity by analyzing one of the distribution areas of PDAM Karawang, namely the Sirnabaya Village community with the results of population growth using the geometric method, namely 67,096 people, the number of community water needs and facilities is 206, 64 l/s, with a pump capacity that includes the effective discharge in operating hours of 0.602 m3/s, the effective discharge of each pump used is 0.200 m3//s, and the theoretical discharge of the pump is 0.217 m3/s. The required pump results are 3 main pumps and 1 backup pump.